2014
DOI: 10.1016/j.econmod.2014.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Building a financial conditions index for the euro area and selected euro area countries: What does it tell us about the crisis?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 14 publications
1
49
0
1
Order By: Relevance
“…The paper argues that FCI can be used as a good indicator to ascertain inflation targets and to monitor development in the Turkish economy. Angelopoulou et al (2014) also constructed a FCI; and they found that for countries, like Greece and Portugal, their financial condition deteriorated after the sovereign crisis and the global financial crisis, when compared with countries like Germany that enjoyed a strong financial condition. Therefore, the effect of financial liberalization can be heterogeneous across the globe.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper argues that FCI can be used as a good indicator to ascertain inflation targets and to monitor development in the Turkish economy. Angelopoulou et al (2014) also constructed a FCI; and they found that for countries, like Greece and Portugal, their financial condition deteriorated after the sovereign crisis and the global financial crisis, when compared with countries like Germany that enjoyed a strong financial condition. Therefore, the effect of financial liberalization can be heterogeneous across the globe.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These include studies, such as Matheson (2012), Koop and Korobilis (2014), Angelopoulou, Balfoussia, and Gibson (2014), and Bulut (2017), amongst others. These papers usually construct a financial conditions index to measure the real state of economic and financial activities, instead of using the traditional interest rate variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, an FCI should cover all the contents about the future state of the economy contained in these current financial variables. Using similar methodology as in constructing an FSI, Angelopoulou et al (2013) summarizes several ways from which the weights of FCIs are generally derived: (1) structural models as in Goodhart et al (2002); (2) reduced form models likely in Mayes and Viren (2001); (3) Principal Components Analysis in Forss et al (2011); (4) impulse responses of a VAR or Kalman filter. FCIs have been developed for a number of countries (US, Canada, Finland, Sweden, Germany, UK, Euro area etc.).…”
Section: Literature Reviewmentioning
confidence: 99%
“…2 Notable exceptions are Angelopoulou et al (2014) and Hatzius et al (2010), where a higher number of factors is explicitly addressed. Their focus, however, is somewhat different as they aim at improving the forecast ability and end up with one aggregate index or do not assess the dimension of underlying shocks, for instance.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably the most prominent index, besides numerous different indices presented in the recent literature. For instance, Davig and Hakkio (2010) and Hakkio and Keeton (2009) construct the Kansas City Financial Stress Index (KCFSI), as well as Angelopoulou et al (2014) build a financial stress index by using principal components analysis (PCA) to capture the co-movement of the underlying series. Dynamic factor econometrics methods are used by Brave and Butters (2011) and Butters (2012), van Roye (2013) and Matheson (2012).…”
Section: Introductionmentioning
confidence: 99%